In the tradition of Andalusia - Razak, Dzulkifli Abd (2011)
AN exhibition of 16 monumental sculptures, which pays tribute to the Nasrid architecture of the notable Alhambra Palace, will be displayed at Madrid’s Reitro Park and Plaza de la Independencia in Spain until the end of April. The display of the sculptures by famous artist Cristóbal Gabarrón is in conjunction with the 15th anniversary of Cristóbal Gabarrón Foundation. The artist’s colourful and contemporary Towers of Alhambra highlighted the multicultural nature of a society where Muslims, Jews and Christians lived harmoniously together.